Age and amyloid effects on human central nervous system amyloid‐beta kinetics. Issue 3 (20th July 2015) - Patterson, Bruce W.; Elbert, Donald L.; Mawuenyega, Kwasi G.; Kasten, Tom; Ovod, Vitaliy; Ma, Shengmei; Xiong, Chengjie; Chott, Robert; Yarasheski, Kevin; Sigurdson, Wendy; Zhang, Lily; Goate, Alison; et al.
<x xml:space="preserve">Abstract</x> Objective Age is the single greatest risk factor for Alzheimer's disease (AD), with the incidence doubling every 5 years after age 65. However, our understanding of the mechanistic relationship between increasing age and the risk for AD is currently limited. We therefore sought to determine the relationship between age, amyloidosis, and amyloid‐beta (Aβ) kinetics in the central nervous system (CNS) of humans. Methods Aβ kinetics were analyzed in 112 participants and compared to the ages of participants and the amount of amyloid deposition. Results We found a highly significant correlation between increasing age and slowed Aβ turnover rates (2.5‐fold longer half‐life over five decades of age). In addition, we found independent effects on Aβ42 kinetics specifically in participants with amyloid deposition. Amyloidosis was associated with a higher (>50%) irreversible loss of soluble Aβ42 and a 10‐fold higher Aβ42 reversible exchange rate. Interpretation These findings reveal a mechanistic link between human aging and the risk of amyloidosis, which may be owing to a dramatic slowing of Aβ turnover, increasing the likelihood of protein misfolding that leads to deposition. Alterations in Aβ kinetics associated with aging and amyloidosis suggest opportunities for diagnostic and therapeutic strategies. More generally, this study provides an example of how changes in protein turnover kinetics can be used to detect physiological and pathophysiological changes and may be applicable to other proteinopathies. Ann Neurol 2015;78:439–453